OP0201 A phase 3 study of the efficacy and safety of ixekizumab in patients with active psoriatic arthritis and inadequate response to tumour necrosis factor inhibitor(s). (15th June 2017) - Nash, P; Kirkham, B; Okada, M; Rahman, P; Combe, B; Adams, DH; Kerr, LN; Lee, CH; Shuler, CL; Genovese, MC
Abstract : Background: Tumour necrosis factor inhibitors (TNF-i) have revolutionised the management of psoriatic arthritis (PsA) yet some patients (pts) have an inadequate response (IR) or intolerance. Ixekizumab (IXE), a monoclonal high affinity antibody that selectively targets IL-17, has shown efficacy in TNF-naïve PsA pts. 1 Objectives: To compare efficacy and safety of IXE with placebo in pts with active PsA who are TNFi-IR. Methods: In the 24 week (wk), double-blind, placebo-controlled period of a Phase 3 PsA study (SPIRIT-P2; NCT02349295 ), pts with prior IR or intolerance to 1 or 2 TNF-i were randomised to SC placebo or IXE 80 mg every 2 (Q2W) or 4 wks (Q4W), following a 160 mg initial dose at Wk 0. Pts with IR to treatment (protocol defined) received rescue therapy at Wk 16. Primary endpoint was ACR20 at Wk 24. Continuous data were analyzed using mixed-effects model for repeated measures; categorical data, using a logistic regression model with missing values imputed by non-responder imputation, which treats IR as non-responders. Results: 363 pts were randomized: ∼52 yrs old on average, female (53%), white (∼92%), and IR to 1 or 2 TNF-i (204 [56.2%], 128 [35.3%], respectively) or TNF-intolerant (31 [8.5%]). Most pts had current psoriasis (93.4%) and BSA≥3 (62.5%). The majority (87%) completed the 24-wk, double-blind period. A significantly higher proportion of IXE- vs placebo-treated pts at Wk 24 achieved ACR20 (65 [53.3%], 59 [48%] vs. 23 [19.5%]; Q4W, Q2W, placebo, respectively), ACR50 (43 [35.2%], 41 [33.3%] vs 6 [5.1%]; Q4W, Q2W, placebo, respectively), ACR70 (27 [22.1%], 15 [12.2%] vs 0; Q4W, Q2W, placebo, respectively), MDA (34 [27.9%], 29 [23.6%] vs 4 [3.4%]; Q4W, Q2W, placebo, respectively), DAS28-CRP, and reductions in functional disability (HAQ-DI) (Table). A significantly higher proportion of IXE-Q4W- vs placebo-treated pts reached complete resolution of dactylitis (LDI-B=0). Although enthesitis improved from baseline with both IXE doses, rates of complete resolution (LEI=0) were not significantly different compared to placebo. At Wk 24, significantly greater proportions of IXE-treated pts with ≥3% BSA achieved PASI 75 than placebo-treated patients. The incidence of treatment-emergent adverse events (TEAE) was similar across groups (83 [68%], 90 [73.2%] vs 76 [64.4%]; Q4W, Q2W, placebo, respectively). A numerically higher proportion of IXE-treated pts reported infection and a significantly higher proportion reported injection site reactions (the majority were mild) (Table). Serious infection (0, 3 [2.4%], 0; Q4W, Q2W, placebo respectively), serious AE, and oral candidiasis were numerically higher with Q2W vs placebo. No deaths or cases of inflammatory bowel disease, uveitis, TB reactivation, or grade ≥3 neutropenia were reported. Conclusions: IXE improved arthritis 1, physical function, and psoriasis 2, 3 vs placebo with no unexpected safety findings in patients with active PsA and prior IR or intolerance to TNF-inhibitor(s). References: Mease PJ et al. Ann Rheum Dis 2016;0:1–9. Gordon BK et al. N Engl J Med 2016;375:345–56. Griffiths CE et al. Lancet 2015; 386:541–51. Disclosure of Interest: P. Nash Grant/research support from: AbbVie, Amgen, BMG, Celgene, Eli Lilly and Company, Hospira, Janssen, MSD, Novartis, Pfizer, Roche, Sanofi, UCB, Consultant for: AbbVie, Amgen, BMS, Celgene, Eli Lilly and Company, Hospira, Janssen, MSD, Novartis, Pfizer, Roche, Sanofi, USB, Speakers bureau: AbbVie, Amgen, BMS, Celgene, Eli Lilly and Company, Hospira, Janssen, MSD, Novartis, Pfizer, UCB, Roche, Sanofi, B. Kirkham Grant/research support from: Arthritis Research UK, AbbVie, Eli Lilly and Company, Roche, UCB, Consultant for: AbbVie, Celgene, Eli Lilly and Company, Janssen, Pfizer, Novartis, M. Okada Consultant for: Eli Lilly and Company, P. Rahman Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Eli Lilly and Company, Janssen, Novartis, Pfizer, B. Combe Grant/research support from: Bristol-Myers Squibb, Celgene, Janssen, Eli Lilly and Company, Merck, Novartis, Pfizer, Roche-Chugai, UCB Pharma, Speakers bureau: Bristol-Myers Squibb, Janssen, Merck, Pfizer, Roche-Chugai, UCB PHarma, D. Adams Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, L. Kerr Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, C. Lee Shareholder of: Eli Lilly and, Employee of: E, C. Shuler Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, M. Genovese Grant/research support from: AbbVie, Astellas, Eli Lilly and Company, Galapagos, Pfizer, Vertex, Consultant for: AbbVie, Astellas, Eli LIlly and Company, Galapagos, Pfizer, Vertex